2018
DOI: 10.21170/geonorte.2018.v.9.n.32.93.106
|View full text |Cite
|
Sign up to set email alerts
|

OS CLIMAS REGIONAIS DO BRASIL (ESTUDO PRELIMINAR)/ The regional climates of Brazil (Preliminary study).

Abstract: Neste estudo escolhemos a classificação climática genética de Oliver (1970), para tratar os dados mensais de temperatura e precipitação de 110 estações meteorológicas (“Normais Climatológicas do Brasil 1961-1990”, INMET, 2009), que foram superpostos ao diagrama de Venn. Por um lado, os resultados preliminares, sintetizados num quadro, apontam para a grande variabilidade climática do Brasil e fornecem informações sobre tipos climáticos regionais que ainda não foram abordados nas contribuições clássicas de Andra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
4
0
4
Order By: Relevance
“…Outra questão importante, e presente em diversas capitais brasileiras, são as Ilhas de Calor. Um estudo demonstrou que os seus efeitos estão fortemente presentes em Brasília, vista a presença de um intenso processo de urbanização em sua região satélite, dos numerosos locais com solo exposto e do desmatamento 39 . Campo Grande, por sua vez, está situada mais ao sul da região Centro -Oeste e apresentou associação para o frio extremo.…”
Section: Discussionunclassified
“…Outra questão importante, e presente em diversas capitais brasileiras, são as Ilhas de Calor. Um estudo demonstrou que os seus efeitos estão fortemente presentes em Brasília, vista a presença de um intenso processo de urbanização em sua região satélite, dos numerosos locais com solo exposto e do desmatamento 39 . Campo Grande, por sua vez, está situada mais ao sul da região Centro -Oeste e apresentou associação para o frio extremo.…”
Section: Discussionunclassified
“…Another important factor in various state capitals in Brazil are the effects of urban heat islands. A study showed that these effects are particularly pronounced in Brasília due to an intense process of urbanization in satellite cities, deforestation and soil exposure 39 . Campo Grande, on the other hand, located further south in the Center-West region, showed an association with extreme cold.…”
Section: 456mentioning
confidence: 99%
“…In Rio de Janeiro and São Paulo, the most populous state capitals in the Southeast, risk of death from cerebrovascular diseases was higher in both cold and hot periods. In both São Paulo, which has a humid subtropical climate (Cfa) 39 , and Rio de Janeiro, which has a tropical wet-dry climate (Aw) 39 , frontal systems and air masses are common, creating distinct trends in air temperature throughout the year. This results in higher variability in temperature, illustrated by a high standard deviation in the air temperature data.…”
Section: 456mentioning
confidence: 99%
See 2 more Smart Citations